Climate Warming Increased Spring Leaf-Out Variation Across Temperate Trees in China - Zhang, Yaru; Fu, Yongshuo; Geng, Xiaojun; Chen, Shouzhi; Guo, Yahui; Wu, Zhaofei; De Boeck, Hans J. (Frontiers in Forests and Global Change, 2021)
Leaf-out phenology plays a key role in ecosystem structure and functioning. Phenological changes have often been linked to climatic factors and have received considerable attention, with most studies focusing on trends of leaf-out phenology. Leaf-out variation, which reflects the stability of phenological responses, may also be affected by climate change, yet this has received less scientific attention. In this study, we examined spring leaf-out variation (LOV) in response to climate change in China during the period 1963 - 2008 using in situ records of 15 species at 25 phenological observation sites across several climate zones, and explored spatio-temporal changes of LOV and the underlying mechanisms. We observed a significant decrease of LOV towards higher latitudes (-0.2 ± 0.1 d·°N-1; P < 0.001) across all species. Temporally, we found that the LOV was significantly increased from the period 1963 - 1986 (6.9 ± 2.8 d) to the period 1987 - 2008 (7.9 ± 3.7 d, P < 0.05). Furthermore, the LOV changes between the period 1987 - 2008 and 1963 - 1986 were significantly smaller at high latitudes (average decrease of 1.0 d) than at low latitudes (average increase of 1.5 d). The spatial pattern of LOV is likely due to both increased heat requirements and greater temperature sensitivity at low latitudes compared to high latitudes. The temporal pattern of LOV is likely related to increased heat requirements for leaf-out during 1987-2008 when the average air temperature was higher. Our analysis indicated that the phenology response to climate change is not only reflected in the temporal trends for long time series, but also in the variation of phenological dates. Results from this study improve our understanding of phenological responses to climate change, and could be applied in the assessment of regional phenology changes to better evaluate the impacts of climate change on ecosystem structure and function.